FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR: DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Septiyani, Glory; Rasyid, Elly; Tobing, Emerald G. (Universitas Kristen Indonesia, 2017)
The purpose of this study to determine the effect of capital structure, earnings growth, and the size of the company to the quality of earnings in the base and Chemical Industry Company listed on the Indonesian Stock Exchange (BEI) in the period 2012-2015. Quality measurement using the model Penman (2001) Quality of earnings. The results of this study indicate simultaneous testing with a significant level of 0.040 <0.05 states that the capital structure, earnings growth and company size affects the quality of earnings in the chemical and basic industry companies listed in the IDX. Partially, the capital structure and have a significant effect on the quality of earnings positive direction with a significant level of 0.049> 0.05 profit growth is not significant, but has a positive direction by showing the significant level of 0.193> 0.05 on earnings quality and size of the company does not effect significantly to the quality of earnings but showed a positive direction towards the quality of earnings with a significant level of 0.182> 0.05Keywords : Capital Structure, Earning growth, Size company, quality of income